Berlin, Deutschland/Olympia, Griechenland. Digital Roofs. Die Arbeiten der Jahre 2020 und 2021 - Fless, Friederike; Rheeder, Annalize (e-Forschungsberichte des DAI, 2021)
The project »digital roofs« has three goals: (1) to develop and test new methods for the digital documentation of roof tile finds, (2) to facilitate the processing and dissemination of unpublished roof tile assemblages and (3) to compile a compendium of well-documented comparative finds. Several departments of the German Archaeological Institute are working together to achieve these goals. The main project, based in Berlin, has developed procedures, methods and techniques that are being tested, discussed and refined on current projects (carried out) by the departments in Athens and Rome.